Management of cardiovascular emergencies during the COVID-19 pandemic. Issue 12 (13th October 2020) - Choudhary, Rahul; Gautam, Dinesh; Mathur, Rohit; Choudhary, Dinesh
Abstract : Background: It has been reported that patients attending the emergency department with other pathologies may not have received optimal medical care due to the lockdown measures in the early phase of the COVID-19 pandemic. Methods: This was a retrospective study of patients presenting with cardiovascular emergencies to four tertiary regional emergency departments in western India during the government implementation of complete lockdown. Results: 25.0% of patients during the lockdown period and 17.4% of patients during the pre-lockdown period presented outside the window period (presentation after 12 hours of symptom onset) compared with only 6% during the pre-COVID period. In the pre-COVID period, 46.9% of patients with ST elevation myocardial infarction underwent emergent catheterisation, while in the pre-lockdown and lockdown periods, these values were 26.1% and 18.8%, respectively. The proportion of patients treated with intravenous thrombolytic therapy increased from 18.4% in the pre-COVID period to 32.3% in the post-lockdown period. Inhospital mortality for acute coronary syndrome (ACS) increased from 2.69% in the pre-COVID period to 7.27% in the post-lockdown period. There was also a significant decline in emergency admissions for non-ACS conditions, such as acute decompensated heart failure and high degree or complete atrioventricular block. Conclusion: The COVID-19 pandemic has led to delays in patients seeking care for cardiac problems and also affected the use of optimum therapy in our institutions.